Long‐term trends in books of terms related to forest pathology1. (27th July 2015) - Pautasso, M.
Abstract : Scientometric and bibliometric methods are increasingly applied to study temporal trends in scientific outputs, but there has been little application in plant and forest health. This research note uses the Google Books N‐Grams search engine to explore temporal trends in the use of terms related to forest pathology in published books. The search was performed for books in American and British English, French, German and Italian. There is evidence for a relative decline in the use of the term 'forest pathology', since the 1950s in books in American English and since the 1990s in books in British English. This decline was counterbalanced by a relative increase in the use of the term 'forest health' between the 1980s and the end of the 1990s, whereas the term 'tree diseases' roughly followed the same trend as 'forest pathology'. A declining trend was observed for 'pathologie forestière' (since the 1980s), both 'Waldschutz' and 'Forstschutz' (since the 1990s), as well as 'patologia forestale' (since the 1950s). The use of the terms 'dendrology', 'forest entomology', 'forest genetics', 'mycology', 'plant pathology' appears to have followed the trend observed for 'forest pathology' in all studied languages. Conversely, there has been an increase in books mentioning topics such as 'ecosystem health' and 'old‐growth forests.' The trends observed here call for increased efforts to make the public aware of trees, their diseases and the health of forests.